3, 3'‐Diindolylmethane suppresses high‐fat diet‐induced obesity through inhibiting adipogenesis of pre‐adipocytes by targeting USP2 activity. Issue 10 (18th July 2017) - Yang, Hee; Seo, Sang Gwon; Shin, Seung Ho; Min, Soyun; Kang, Min Jeong; Yoo, Ra; Kwon, Jeong Yeon; Yue, Shuhua; Kim, Kee Hong; Cheng, Ji‐Xin; Kim, Jong Rhan; Park, Joon‐Suk; et al.
Abstract : Scope: Indole‐3‐carbinol (I3C), a derivative abundant in cruciferous vegetables such as cabbage, is well known for its various health benefits such as chemo‐preventive and anti‐obesity effects. I3C is easily metabolized to 3, 3′‐diindolylmethane (DIM), a more stable form, in acidic conditions of the stomach. However, the anti‐obesity effect of DIM has not been investigated clearly. We sought to investigate the effect of DIM on diet‐induced obesity and to elucidate its underlying mechanisms. Methods and results: High‐fat diet (HFD)‐fed obese mouse and MDI‐induced 3T3‐L1 adipogenesis models were used to study the effect of DIM. We observed that the administration of DIM (50 mg/kg BW) significantly suppressed HFD‐induced obesity, associated with a decrease in adipose tissue. Additionally, we observed that DIM treatment (40 and 60 μM), but not I3C treatment, significantly inhibited MDI‐induced adipogenesis by reducing the levels of several adipogenic proteins such as PPAR‐γ and C/EBPα. DIM, but not I3C, suppressed cell cycle progression in the G1 phase, which occurred in the early stage of adipogenesis, inducing post‐translational degradation of cyclin D1 by inhibiting ubiquitin specific peptidase 2 (USP2) activities. Conclusion: Our findings indicate that cruciferous vegetables, which can produce DIM as a metabolite, have the potential to prevent or treat chronic obesity. Abstract : The anti‐obesity effect of 3, 3'‐diindolylmethane (DIM) in high‐fat diet (HFD)‐fed obese mice can be attributable to a decrease in adipose tissue. These changes by DIM treatment are associated to inhibition of adipogenesis of pre‐adipocytes by suppressing cell cycle progression in the G1 phase resulting from the post‐translational degradation of cyclin D1 by inhibiting ubiquitin specific peptidase 2 (USP2) activities. While indole‐3‐carbinol (I3C), a precursor of DIM abundant in cruciferous vegetable such as cabbage, treatment does not exert anti‐adipogenic activity at the same concentration.